ANALISIS SENSORIS KOPI LOKAL DALAM PREFERENSI MAHASISWA JATINANGOR DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP - Kezia Janice Megakomatchi; Totok Pujianto; Devi Maulidah Rahmah (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Coffee consumption has become integral to student lifestyles, particularly in Jatinangor, an educational hub with a high student population. This study aims to analyze Jatinangor students' preferences for local coffee variants based on sensory criteria: aroma, acidity level, and aftertaste. The Analytical Hierarchy Process (AHP) method was employed to evaluate five local coffee variants (Arabika Manglayang, Arabika Sidikalang, Liberika Meranti, Robusta Flores, and Robusta Bali Kintamani) through organoleptic tests involving 100 student respondents. Results indicate Robusta Flores as the top-priority variant (27%) across all criteria, followed by Liberika Meranti (22%) and Robusta Bali Kintamani (21%), while Arabika Sidikalang ranked lowest (14%). Consistency Ratio (CR) values below 0.1 confirm result reliability. The analysis consistently demonstrates Robusta Flores' superiority in meeting students' sensory preferences, making it a key reference for local coffee product development.